Notes from the Low Vision Gallery - Kuusisto, Stephen (Disability Studies Quarterly, 2013)
The author describes some experiences as a blind visitor to The Prado in Madrid, the Museum of Modern Art in New York, and elsewhere. Key words: blindness, blind museum access, Prado, Museum of Modern Art